Transgressive incidents targeted on staff in forensic psychiatric healthcare: a latent class analysis - Frowijn, Iris; Masthoff, Erik; Vermunt, Jeroen K.; Bogaerts, Stefan (Frontiers in Psychiatry, 2024)
Transgressive incidents directed at staff by forensic patients occur frequently, leading to detrimental psychological and physical harm, underscoring urgency of preventive measures. These incidents, emerging within therapeutic relationships, involve complex interactions between patient and staff behavior. This study aims to identify clusters of transgressive incidents based on incident characteristics such as impact, severity, (presumed) cause, type of aggression, and consequences, using latent class analysis (LCA). Additionally, variations in incident clusters based on staff, patient, and context characteristics were investigated. A total of 1,184 transgressive incidents, reported by staff and targeted at staff by patients between 2018-2022, were extracted from a digital incident reporting system at Fivoor, a Dutch forensic psychiatric healthcare organisation. Latent Class Analysis revealed six incident classes: 1) verbal aggression with low impact; 2) verbal aggression with medium impact; 3) physical aggression with medium impact; 4) verbal menacing/aggression with medium impact; 5) physical aggression with high impact; and 6) verbal and physical menacing/aggression with high impact. Significant differences in age and gender of both staff and patients, staff function, and patient diagnoses were observed among these classes. Incidents with higher impact were more prevalent in high security clinics, while lower-impact incidents were more common in clinics for patients with intellectual disabilities. Despite limitations like missing information, tailored prevention approaches are needed due to varying types of transgressive incidents across patients, staff, and units.